Identifikasi Kelelawar Berdasarkan Morfologi dan Morfometri di Kawasan Kampus Universitas Sriwijaya, Indralaya - Intan Qaanitah; Indra Yustian; Mustafa Kamal (Jurnal Penelitian Sains, 2018)
This research is to know the kind of bats based on morphology and morphometry identification in campus area of Sriwijaya University, Indralaya. The research was conducted at campus area of Sriwijaya University, Indralaya and the specimen was preserved at Animal Taxonomy Laboratory of Biology Department of FMIPA Sriwijaya Universi-ty. The research method used is the installation mist net traps in four location that is area of biology department, lecturer housing, mushollah area FMIPA, and the front gate of UNSRI. The installation was conducted in afternoon from 5-9 pm. The catch results obtained 104 bats consisting of three types of fruit eaters, that is 57 Cynopterus brachyotis with mor-phometry average mass 27.80 gram, whole body 74.90 mm, tail 13.27 mm, ear 17.19 mm, whole feet 13.94 mm, fore arm 63.05 mm, dan tibia 23.84 mm, 14 Cynopterus sphinx with morphometry average mass 32.84 gram, whole body 82.45 mm, tail 13.37 mm, ear 18.09 mm, whole feet 15.04 mm, fore arm 65.32 mm, dan tibia 24.36 mm, one Rousettus amplex-icaudatus with morphometry mass 67.5 gram, whole body 95.6 mm, tail 19.5 mm, ear 21.5 mm, whole feet 20.8 mm, fore arm 70.8 mm, dan tibia 37.4 mm; one type of insectivorous 31 Chaerephon plicatus with morphometri average mass 14.35 gram, whole body 62.64 mm, tail 44.17 mm, ear 20.52 mm, whole feet 10.31 mm , fore arm 48.02 mm, dan tibia 37.4 mm; and one type of nectar eater one Macrglossus sobrinus with morphometry mass 20 gram, whole body 62.7 mm, tail 0 mm, ear 14.8 mm, whole feet 12 mm, fore arm 45.6 mm, dan tibia 21.5 mm.